Asuhan Akupunktur pada Kasus Frozen Shoulder di Praktik Mandiri Ionetherapy Semarang - Iwan Isbikhan; Ikhwan Abdullah; Leny Candra Kurniawan; Mayang Wulandari (Universitas Malahayati Lampung, 2026)
ABSTRACT The upper extremities play a crucial role in almost all daily activities, and frozen shoulder is a condition characterized by restricted shoulder movement. Frozen shoulder presents with varying degrees of severity, ranging from mild to severe pain, as well as differing levels of limitation in the range of motion of the glenohumeral joint. Acupuncture has been widely used and proven effective in the management of frozen shoulder, particularly in reducing pain, decreasing stiffness, and improving patients’ quality of life. This case study aimed to determine the benefits of acupuncture care for a frozen shoulder case at the Ionetherapy Independent Practice in Semarang. The study was conducted as a single-case study over six therapy sessions involving one male participant aged 45 years who had been experiencing frozen shoulder for the past two weeks. Data collection techniques included observation (Wang), interview (Wen), listening and smelling (Wen), and palpation (Qie), in accordance with the standards of Traditional Chinese Medicine. The selection of acupuncture points was based on the syndrome of Qi and Blood Stagnation, with therapeutic principles focused on relieving pain and promoting the smooth flow of Qi and Blood. The evaluation results showed gradual and consistent improvement, including a progressive reduction in shoulder pain and stiffness until the symptoms resolved by the sixth therapy session, accompanied by an increased range of shoulder motion and improved ability to perform daily activities without limitation. Keywords: Frozen Shoulder, Acupuncture Therapy, Qi and Blood Stagnation. ABSTRAK Anggota gerak atas memiliki keterlibatan yang sangat tinggi dalam semua aktifitas, frozen shoulder termasuk kondisi dimana gerakan bahu menjadi terbatas. Frozen Shoulder memiliki tingkatan kepararahan yang bervariasi mulai dari nyeri ringan sampai berat dan tingkatan keterbatasan seberapa besar terhadap gerakan sendi glenohumeral. Akupunktur telah banyak digunakan dan terbukti efektif dalam pananganan Frozen Shoulder, terutama dalam menurunkan nyeri, menurunkan kekakuan, dan memperbaiki kualitas hidup pendritanya. Penelitian studi kasus ini bertujuan untuk mengetahui manfaat Asuhan Akupunktur pada Kasus Frozen Shoulder di Praktik Mandiri Ionetherapy Semarang. Penelitian dilakukan dalam bentuk studi kasus tunggal selama enam sesi terapi pada satu orang partisipan laki-laki berusia 45 tahun yang mengalami Frozen Shoulder sejak 2 minggu yang lalu. Teknik pengumpulan data meliputi observasi (Wang), wawancara (Wen), pendengaran dan penciuman (Wen), dan perabaan (Qie) sesuai standar ilmu pengobatan Tiongkok. Pemilihan titik akupunktur didasarkan pada sindrom Stagnasi Qi dan Darah dengan prinsip terapi yang diterapkan adalah mengilangkan nyeri, memperlancar Qi dan Darah. Hasil evaluasi terapi menunjukkan adanya perbaikan yang bertahap dan konsisten, seperti berkurangnya nyeri dan kekakuan bahu secara bertahap hingga keluhan menghilang pada terapi keenam, disertai dengan meningkatnya rentang gerak bahu dan kemampuan melakukan aktivitas sehari-hari tanpa hambatan. Kata Kunci: Frozen Shoulder,Terapi Akupunktur, Stagnasi Qi dan Darah.